Classical reception in animation: a case study of the effect of target audience age in Disney’s Hercules and Netflix’s Blood of Zeus - Kamper, Femia (Stellenbosch : Stellenbosch University, 2024)
Thesis (MA)--Stellenbosch University, 2024.